Massive Intercalary Reconstruction of Lower Limb after Wide Excision of Malignant Tumors: An Alternative to Amputation or Rotationplasty - Shin, Seung Han; Lee, Keun-Ho; Jang, Seung Pil; Mun, Goo-Hyun; Seo, Sung Wook (Journal of Reconstructive Microsurgery, 2014)
In this study, we present the feasibility of intercalary limb resection and massive reconstruction for malignant tumors of lower extremity. Ten cases of lower extremity malignancies that had undergone concomitant bone (and/or joint) and soft-tissue reconstruction after wide excision exceeding two-thirds of the cross-sectional area of the affected limb were reviewed. All cases were indicated for amputation because of an expansive tumor, hematoma from a pathologic fracture, or previous unplanned excision, with or without critical structure involvement. Bone was reconstructed with either an allograft or a tumor prosthesis. Soft-tissue reconstruction was performed to achieve critical structure and coverage, which was required in all cases. The resection margin was clear in all cases, and no soft-tissue graft failure was encountered. During a mean follow-up of 26 months (range, 9–42 months), no patient developed local recurrence in the resection–reconstruction site. Of the 10 patients, 8 patients were able to walk independently, and two were ambulatory but needed crutch support outdoors. Massive intercalary resection and reconstruction can be an effective treatment option for locally progressed or complicated lower extremity malignancies. Considering patient preference and the fair functional outcomes observed, it may be a useful alternative to amputation or rotationplasty.
Keywords: massive intercalary reconstruction; intercalary limb resection; limb salvage surgery; amputation; rotationplasty